Pengaruh Work-Life Balance Dan Efektivitas Komunikasi Terhadap Employee Engagement Dengan Dukungan Manajerial Sebagai Variabel Moderasi Pada PT. PLN Unit Induk Distribusi Sumatera Barat - Afpuadi Nur (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the influence of work-life balance and communication effectiveness on employee engagement, with managerial support as a moderating variable at PT. PLN West Sumatra Distribution Main Unit. The study is motivated by the level of employee engagement that has not yet reached the company's target, potentially affecting organizational performance. The research method used is quantitative, involving the distribution of questionnaires to 60 respondents selected from a population of 150 employees using a purposive sampling technique. The research variables consist of work-life balance and communication effectiveness as independent variables, employee engagement as the dependent variable, and managerial support as the moderating variable. The results show that work-life balance and communication effectiveness have a positive and significant effect on employee engagement, managerial support moderates the effect of work-life balance on employee engagement, but managerial support does not moderate the effect of communication effectiveness on employee engagement. This study is expected to contribute to the development of Human Resource Management knowledge and serve as a consideration for PT. PLN West Sumatra Distribution Main Unit in enhancing employee engagement.